Absorption cleaning of fuel gases in an activated carbon production plant - Gilfanov K. K.; Safin R.G.; Sotnikov V. G. (BIO Web of Conferences)
Today, waste recycling in Russia is becoming increasingly important, since new, in-demand products are obtained during their recycling. But for many enterprises, recycling of production waste is becoming impossible due to many constraints, the key one being environmental pollution during the recycling of this waste. The most effective and environmentally friendly method of recycling waste is its thermochemical decomposition into coal, combustible gas and liquid fuel. But even with pyrolysis, which is quite safe for the environment, emissions of harmful substances occur that pollute the atmosphere. The solution to the problem of emissions of harmful impurities is sorption gas purification systems. During adsorption purification, gas with harmful impurities is passed through a solid material with a high specific surface area, during absorption purification, the gas is purified using a liquid component that absorbs harmful particles of gas emissions. The price of adsorbents is quite high and requires frequent replacement due to rapid saturation, therefore this paper presents an absorption system for cleaning flue gases, implemented in a pyrolysis waste processing plant. The principle of the absorber is to repeatedly pass the absorbent through gas emissions. The purified gas is harmless to the environment and can be safely released into the atmosphere.